The Impact of the COVID-19 Pandemic on the Prevalence and Severity of Internet Addiction: Current and Future Public Health Challenges - Bashir M. Rezk; Illya Tietzel (Public Health, 2025)
The coronavirus disease-2019 (COVID-19) pandemic altered the lifestyle of a substantial number of individuals who were compelled to undergo quarantine in their residences. Consequently, they relied heavily on the Internet for studying, online teaching, official meetings, communication, entertainment, conferences, and work. There is a possibility that the pandemic has led to a greater inclination towards internet addiction compared to both pre-pandemic and post-pandemic periods. Internet addiction is a behavioral disorder characterized by excessive and compulsive internet use that interferes with daily life activities. The prevalence of internet addiction has been a concern for several years, with an increasing number of people spending con-siderable amounts of time online. Several studies provide evidence that the occurrence of internet addiction varies significantly across countries and cultures, with certain regions demonstrating higher rates than others. This review reveals a substantial surge in the prevalence of internet addiction during the COVID-19 pandemic. The most notable discovery is that internet addiction has undergone an almost threefold increase during the COVID-19 pandemic when compared to its occurrence in the previous decade. During the COVID-19 pandemic, Nigeria had the highest recorded prevalence rate of internet addiction, reaching 88.1%. In contrast, Turkey had the lowest observed rate of internet addiction at 4.8%. Accordingly, we stress the importance of enhancing our awareness to recognize internet addiction as a novel global syndrome arising from progressively complex public health and psychosocial circumstances.